The IMPACT OF COVID-19 PANDEMIC ON LEARNING OF UNDERGRADUATE MEDICAL STUDENTS: A CROSS-SECTIONAL STUDY FROM KARACHI - Adina Anwar (Army Medical College Rawalpindi, 2020)
Objective: To assess the impact of COVID-19 pandemic on learning of undergraduate medical students of Karachi.